تحسين العمليات التشغيلية في صناعة الإسمنت باستخدام منهجية Six Sigma: دراسة حالة باستخدام تقنية Deming (Comprehensive Journal of Science, 2025)
The cement industry is a vital sector facing significant challenges related to operational efficiency, product quality, and environmental impact. This study aims to evaluate the effectiveness of applying the Six Sigma methodology in improving operational processes within the cement industry, focusing on critical factors and associated challenges, and integrating Deming Technique as a supportive framework. The research adopted a descriptive-analytical approach. Data was collected from Al-Burj Cement Plant in Zliten, Libya, during April 2025, through questionnaires and interviews with officials and employees. Quantitative data was analyzed using regression analysis and t-tests in SPSS, while qualitative data was analyzed using content analysis. The results indicated that awareness of Six Sigma application remains limited (only 37.14% have knowledge), and the plant's implementation rate was low (31.43%). The study also revealed that the main challenges include insufficient training (57.14%) and a lack of management support (45.71%). Conversely, effective leadership (77.14%) and effective communication (71.43%) were identified as crucial for overcoming these challenges. Despite these hurdles, the majority of participants acknowledged Six Sigma's potential contribution to improving product quality (51.43%), enhancing operational stability (48.57%), and improving safety (51.43%). The study confirms the promising potential of Six Sigma in the cement industry and recommends the necessity of strengthening management support and comprehensive training to ensure its successful future implementation.
Keywords: Six Sigma methodology; improving operational processes; cement industry; Al-Burj Cement Plant